ASSOCIATION BETWEEN INFANT SEX AND BIRTH WEIGHT WITH STUNTING - Suhaid, Dewi Novitasari; Kadarsih, Mitra; Dini, Kusuma; Anggraeni, Lina Dewi; Wardani, Dyah Woro Kartiko Kusumo (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Stunting remains a pressing global health issue, particularly in low- and middle-income countries, where early-life risk factors significantly influence growth trajectories. Among these, infant sex and birth weight are frequently examined as predictors of impaired linear growth. This study aimed to analyze the association between infant sex and birth weight with the incidence of stunting among children aged 6–59 months. A cross-sectional study was conducted involving 127 children aged 6–59 months from “x” village at north sumatera. Stunting was defined according to the World Health Organization growth standards (height-for-age z-score < -2 SD). Independent variables included infant sex (male or female) and birth weight categorized as low birth weight (LBW < 2,500 g) or normal (2,500 – 4,000 g). Chi-square tests were used to assess associations, with statistical significance set at p < 0,05. The prevalence of stunting in the study population was 34,6%. Birth weight demonstrated a statistically significant association with stunting (p = 0,048). Among children with low birth weight, 66,7% were stunted compared to 22,3% among those with normal birth weight. In contrast, infant sex was not significantly associated with stunting (p = 0,094), although a higher proportion of male children (43,6%) were stunted compared to females (27,8%). Low birth weight is significantly associated with an increased risk of stunting in early childhood. Infant sex was not a statistically significant factor in this study. These findings highlight the critical need for antenatal interventions targeting maternal nutrition to prevent low birth weight and reduce the risk of stunting.